Linolein-2-Stearin Phosphate and Linolenic Acid ?-D-Glucoside: The Newer Isolates of Alpinia galanga Rhizomes - B. JAJU, SHIVKANYA; INDURWADE, N.H.; SAKARKAR, D.M.; ALI, M.; FULORIA, N.K.; DURAGKAR, N.J. (Asian Journal of Chemistry, 2010)
Alpinia galanga willd rhizome on chemical analysis and sequential chromatography explored two newer compounds, Linolein-2-stearin phosphate and linolenic acid β-D-glucoside. Structures of newer compounds were elucidated by various spectral techniques (UV, IR, 1H NMR, 13C NMR and MS).